On N.V.Lartseva and Her Speech at Tsvetaeva- Readings in Yerevan. - GEVORGYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The author presents N.V.Lartseva as a literary and cultural worker, an expert in Tsvetaeva’s biography and poetry and makes known her speech in Russian-Armenian (Slavonic) University (Yerevan, 2002).
Keywords: Tsvetaeva-Readings, Yerevan, Lartseva, Petrozavodsk, literary-cultural work, collections